Paul Feyerabend’s Contribution: The Anarchic Sunset of the Philosophy of Science - Benvenuto, Sergio (Filozoficzne Aspekty Genezy, 2024)
Abstract: The author places Feyerabend's contribution within a line of thought on science that ideally opens with the Wienerkreis, and which in some way ends with Feyerabend. This trend has always been based on a series of demarcations, ranging from the opposition between meaningful and meaningless statements (the Vienna Circle), or between scientific and non-scientific statements (Popper), or between normal and extraordinary science (Kuhn), to the demarcation between progressive and regressive research programs (Lakatos) — up until Feyerabend, the former student of Popper, who puts an end to the perspicuity of every demarcation. The conclusion that “anything goes” when it comes to doing rigorous science marks the clearly unsuccessful conclusion of this large-scale historical trend. Philosophical attention thus shifts from descriptions of the scientific method to an analysis of the concrete historical production of scientific ideas and discoveries, in a movement that rehabilitates a Hegelian, historical approach in the empirical sciences. The author outlines the contemporary approach that no longer sees the whole of knowledge and scientific practice as a series of methodologies aimed at faithfully mirroring nature, construing it instead as a thought-constituted organism subject to Darwinian criteria of selection and mutation. The biological metaphor of the organism that survives by adapting to external reality replaces the claim to foundational scientific validity on the basis of a priori paradigms.